Dissection of the molecular targets and signaling pathways of Guzhi Zengsheng Zhitongwan based on the analysis of serum proteomics - Baojin Yao; Jia Liu; Duoduo Xu; Daian Pan; Mei Zhang; Daqing Zhao; Xiangyang Leng (BMC, 2019)
Abstract Background Guzhi Zengsheng Zhitongwan (GZZSZTW) is an effective formula of traditional Chinese herbal medicine and has been widely applied in the treatment of joint diseases for many years. The aim of this study was to dissect the molecular targets and signaling pathways of Guzhi Zengsheng Zhitongwan based on the analysis of serum proteomics. Methods The Chinese herbs of GZZSZTW were immersed in 5 l distilled water and boiled with reflux extraction method. The extract was filtered, concentrated and freeze-dried. The chemical profile of GZZSZTW extract was determined by high-performance lipid chromatography (HPLC). The 7-week old Sprague-Dawley (SD) rats in GZZSZTW groups were received oral administration at doses of 0.8, 1.05, and 1.3 g/kg per day and the rats in blank group were fed with drinking water. Serum samples were collected from the jugular veins. Primary chondrocyte viability was evaluated by CCK-8 assay. A full spectrum of the molecular targets and signaling pathways of GZZSZTW were investigated by isobaric tags for relative and absolute quantitation (iTRAQ) analysis and a systematic bioinformatics analysis accompanied with parallel reaction monitoring (PRM) and siRNA validation. Results GZZSZTW regulated a series of functional proteins and signaling pathways responsible for cartilage development, growth and repair. Functional classification analysis indicated that these proteins were mainly involved in the process of cell surface dynamics. Pathway analysis mapped these proteins into several signalling pathways involved in chondrogenesis, chondrocyte proliferation and differentiation, and cartilage repair, including hippo signaling pathway, cGMP-PKG signaling pathway, cell cycle and calcium signaling pathway. Protein-protein interaction analysis and siRNA knockdown assay identified an interaction network consisting of TGFB1, RHO GTPases, ILK, FLNA, LYN, DHX15, PKM, RAB15, RAB1B and GIPC1. Conclusions Our results suggest that the effects of GZZSZTW on treating joint diseases might be achieved through the TGFB1/RHO interaction network coupled with other proteins and signaling pathways responsible for cartilage development, growth and repair. Therefore, the present study has greatly expanded our knowledge and provided scientific support for the underlying therapeutic mechanisms of GZZSZTW on treating joint diseases. It also provided possible alternative strategies for the prevention and treatment for joint diseases by using traditional Chinese herbal formulas.